JO MARCH’S SPEECH ACT IN GRETA GERWIG’S FILM LITTLE WOMEN - Maharani, Dinda Putri (Fakultas Ilmu Budaya, Universitas Padjadjaran, 2026)
This study investigates the pragmatic function of speech acts performed by Jo March in Greta Gerwig’s film Little Women (2019). By adopting a qualitative descriptive approach, this research analyzes Jo’s utterances using Speech Act Theory and feminist linguistic perspectives to explore how her language reflects resistance to 19th-century gender norms. Data were collected through transcription of selected scenes and categorized using Searle’s taxonomy—assertives, directives, commissives, expressives, and declarations. A feminist reading was applied to examine how each speech act functions to assert identity and challenge patriarchy. The analysis reveals that Jo’s utterances express autonomy, emotional depth, and social critique, reflecting the broader feminist agenda embedded in her linguistic choices. Her speech not only conveys personal aspirations but also becomes a performative act of resistance, making her character a powerful voice for gender equality in modern cinema.